Effect of Number of Impacts on the Voids of AC-WC Mixture with Cement Additive as Filler - Riski, Muhammad; Azwansyah, Heri; Mukti, Elsa Tri (Fakultas Teknik Universitas Tanjungpura, 2025)
This study investigates the effect of the number of compaction impacts on the void characteristics of Asphalt Concrete-Wearing Course (AC-WC) mixtures with cement as an additive filler. The research employed an experimental approach, testing mixtures with two filler types: stone dust alone and a combination of stone dust with 1% cement. Compaction levels varied at 2×65, 2×75, and 2×85 blows, and Marshall tests were conducted to evaluate stability, flow, Voids in Mix (VIM), Voids in Mineral Aggregate (VMA), and Voids Filled with Bitumen (VFB). Results demonstrated that increasing compaction effort and adding 1% cement reduced VIM and VMA while enhancing stability and VFB. The lowest VIM (2.53%) and highest stability (1078.45 kg) were achieved with 6.5% asphalt, 1% cement, and 2×85 blows, indicating improved mixture density and load resistance. The findings align with Bina Marga 2018 specifications, highlighting the benefits of cement as a filler and optimal compaction for AC-WC performance.